Implementasi Teknologi Digital dalam Pengelolaan Pariwisata Berbasis Komunitas Lokal di Kabupaten Enrekang - Hidayat Djabbari, Muhammad; Arnika, Mita; B, Irfan.; Yanto, Erwing (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
Although the region has significant tourism potential, its management is still limited to conventional approaches, thus requiring the implementation of digital technology to improve efficiency and competitiveness. The results of the study indicate that the implementation of digital technology in the tourism sector of Enrekang Regency has begun through the adoption of the QRIS cashless payment system, the use of social media for promotion, and the development of the Enrekang Endless Journey application. However, the application of technology remains limited, as many tourist attractions still rely on manual systems. Therefore, it is crucial to strengthen regional regulations that govern data integration and tourism payment systems, as well as to enhance the capacity of community human resources through training in digital management and online content development. Therefore, to achieve sustainable tourism governance that adapts to technological advancements, we need a well-planned, collaborative, and community-based digital transformation strategy. The conclusion of this study is that the implementation of digital technology in the management of community-based tourism has shown progress, but still requires strengthening in the areas of regulation, infrastructure, and capacity building of human resources to ensure the sustainability and success of technology implementation in community-based tourism.